Aspectos da geometria neutra - Silva, Adriane Renófio da [UNESP] (2015)
In this work we study some aspects of Neutral Geometry, so called because it is not assumed the Axiom of Parallels. We present results which are possible to be demonstrated assuming some axioms Incidence, Betweenness, Congruence and Measure are developed. We demonstrate the Saccheri-Legendre theorem and show that this geometry can not guarantee the existence of rectangles. We are not interested to construct an axiomatic theory, in the strict sense of the word